Risk factors for postoperative complications in Crohn disease: analysis of 173 patients - Melo-Pinto,Diogo (2018)
ABSTRACT Background and objectives: Surgery for Crohn disease has a wide range of factors that are being studied as possible risk factors for postoperative complications. The later are a major problem in those patients and are associated with longer hospital stays and increased mortality and morbidity. Despite the debate regarding the influence of patients' characteristics, preoperative and operative details, the risk factors are not fully identified. The debate has been focused on the new medical therapy and the time of surgery. Our goal was to help identify and confirm risk factors for postoperative complications. Materials and methods: A retrospective cohort study including all patients operated due to Crohn disease in São João Hospital Center from 2010 to 2015. We analyzed patient, preoperative and surgical characteristics. For postoperative complications data only those occurring within 30 days were included. Results: Neither age at diagnosis or previous corticotherapy/anti-TNF/ustekinumab was significantly associated with an increased risk in postoperative complications. Only age at surgery >40 years (Montreal Classification A1 + A2 vs. A3; OR = 4.12; p < 0.05) and the group others (occlusion vs. others [combination of intestinal perforation, mesenteric ischemia and postoperative complications] vs. fistula/abscess as indication for surgery; OR = 4.12; p < 0.05) remained as independent risk factors after multivariable regression analysis. Conclusions: We described clear associations between age at surgery >40 years and the group others (intestinal perforation, mesenteric ischemia and postoperative complications) and overall postoperative complications in Crohn disease. These results may suggest that surgery does not need to be delayed and, in some cases, should be anticipated.